(3GdehVM aj JYdjd hLhg GdbQBGJs - (3GdegOhj , CMeO Hf YeGQ Hf CHj GdYHGS GdegOhj, CHh GdYHGS,J (B440 (3g` s ((3eOjfI MdH s)
(3ChdgG (B:s
(3bGd CHh GdYHGS CeG HYO MeO Gddg HLejY eMGeOg hbO SCdfi SGFdhf Cf Cedi Ydjge cJGHkG eNJUQG ai TQM hLhg GdbQBGJ s
(3BNQgG (B:s
(3MeGdI GdMWH (B: (3GdfUH Ydi GdPe hGdQaY Ydi Cf GeQGI QaY HGdGHJOGA hMeGdI NHQg hEScGf GdgGA haJMgG ai CHj dgH GaJGf ced LejY GdOjhGf s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B184 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B27s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(139(3b(B) s
Keywords: (3GdbQGAGJ hGdJLhjOs